2011
DOI: 10.1111/j.2042-7158.2010.01175.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute renal failure induced by uranyl nitrate on the pharmacokinetics of liquiritigenin and its two glucuronides, M1 and M2, in rats

Abstract: U-ARF rats displayed decreased urinary excretion of LQ glucuronides, resulting in significantly greater AUC and metabolite ratios of M1 and M2 following LQ administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…While, LigF selectively binds to ERβ confirming previous reports [25], [41], 8-PN has high affinity for both ER subtypes [12]. LigF has also been reported to selectively activate ERβ in functional assays [25], [58] which shows not only its selective binding towards ERβ, but also an activating role for ERβ dependent pathways. Selective activation of ERβ by estrogenic ligands has been reported to be correlated with down-regulation of ERα activities, including proliferation [59].…”
Section: Discussionsupporting
confidence: 86%
“…While, LigF selectively binds to ERβ confirming previous reports [25], [41], 8-PN has high affinity for both ER subtypes [12]. LigF has also been reported to selectively activate ERβ in functional assays [25], [58] which shows not only its selective binding towards ERβ, but also an activating role for ERβ dependent pathways. Selective activation of ERβ by estrogenic ligands has been reported to be correlated with down-regulation of ERα activities, including proliferation [59].…”
Section: Discussionsupporting
confidence: 86%
“…38 Liquiritigenin and isoliquiritigenin are flavonoids. 39 They have various pharmacological properties, such as anti-inflammatory, antioxidant and detoxification effects. Zhu et al found that liquiritigenin can attenuate high glucose-induced mesangial matrix accumulation, inflammation and oxidative stress in HBZY cells by suppressing the NFκB and NLRP3 inflammasome signaling pathways.…”
Section: Potential Active Compounds Screening and Identificationmentioning
confidence: 99%
“…The achiral pharmacokinetics of liquiritigenin, and its corresponding glycosides have been reported in the literature (17). Differences in the disposition of an individual enantiomer may result in significant differences in their health benefits or toxic effects in humans (18192021222324252627). The chiral pharmacokinetics of liquiritigenin have only been preliminarily evaluated by our laboratory and one other group.…”
Section: Introductionmentioning
confidence: 99%